2018
DOI: 10.2196/10007
|View full text |Cite
|
Sign up to set email alerts
|

A Mobile App for the Self-Report of Psychological Well-Being During Pregnancy (BrightSelf): Qualitative Design Study

Abstract: BackgroundMaternal mental health impacts both parental well-being and childhood development. In the United Kingdom, 15% of women are affected by depression during pregnancy or within 1 year of giving birth. Suicide is a leading cause of perinatal maternal mortality, and it is estimated that >50% of perinatal depression cases go undiagnosed. Mobile technologies are potentially valuable tools for the early recognition of depressive symptoms, but complex design challenges must be addressed to enable their use in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
60
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 44 publications
1
60
0
6
Order By: Relevance
“…Another reason may be the short duration of the study. Although monitoring could lead to earlier interventions and a better relationship between the patient and the clinician, this study may not have been long enough for improvement to be observed.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Another reason may be the short duration of the study. Although monitoring could lead to earlier interventions and a better relationship between the patient and the clinician, this study may not have been long enough for improvement to be observed.…”
Section: Discussionmentioning
confidence: 99%
“…They allow the user to record symptoms at set intervals over time. Individuals with mental illness are generally open to the use of mobile technology, and point to self‐awareness and communication between patients and clinicians as reasons for engaging in self‐monitoring . Visualization of symptom patterns over time may also be considered a specific strategy for increasing engagement .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations